Realizing An Inclusive Policy For Persons with Disabilities in Indonesia Through The Art of Expressionism Gesture Photography - Fauzi, Muhammad; Wicaksana, Harits Hijrah (Jurnal Manajemen Pelayanan Publik, 2024)
Inclusiveness of people with disabilities is a global issue related to equal rights and opportunities for active participation. The art of gesture photography is a medium to realize this. So, how to make it happen? Using descriptive qualitative research methods and an ethnographic approach, as well as the implementation model of Van Meter and Van Horn as the basis for data analysis. The results of the research show that there is quite a lot of potential for photography artists with disabilities in Indonesia, the absence of a specific policy has resulted in less than optimal implementation. The mistake of forming the KND, which was non-structural and independent, was to make it part of the Ministry of Social Affairs. The government needs to involve people with disabilities in making policies and not only focus disability issues on social issues, but more broadly on human rights issues.